HUBUNGAN ANTARA PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI DENGAN SIKAP TERHADAP PERILAKU SEKSUAL PADA SISWA KELAS XII - Frida Nurlaeli; Dini Rakhmawati (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
This research is motivated by teenagers experiencing changes in values, attitudes and behavior about sexuality that are very fast and confusing as well as cases of free sex in adolescents. The main problem is seeing the relationship between adolescent knowledge about reproductive health and attitudes towards sexual behavior in students in SMK?. The purpose of this study was to determine the relationship between adolescent knowledge about reproductive health and attitudes towards adolescent sexual behavior in class XII students at SMK. This research method is ex-post facto quantitative. The population in this study were all students of SMK LPI Semarang in class X, XI, and XII, totaling 145 students. The technique used is saturated sampling. Collecting data using a reproductive health knowledge questionnaire and a psychological scale of attitudes towards sexual behavior through google form. The results show that this study tcount is greater than ttable (-5.611 > 1.981) with a significance level of 5% (0.05), it can be concluded that Ha is accepted, namely